Impact of Rituximab Desensitization on Blood‐Type‐Incompatible Adult Living Donor Liver Transplantation: A Japanese Multicenter Study. Issue 1 (26th November 2013) - Egawa, H.; Teramukai, S.; Haga, H.; Tanabe, M.; Mori, A.; Ikegami, T.; Kawagishi, N.; Ohdan, H.; Kasahara, M.; Umeshita, K.
Abstract We evaluated the effects of rituximab prophylaxis on outcomes of ABO‐blood‐type‐incompatible living donor liver transplantation (ABO‐I LDLT) in 381 adult patients in the Japanese registry of ABO‐I LDLT. Patients underwent dual or triple immunosuppression with or without B cell desensitization therapies such as plasmapheresis, splenectomy, local infusion, intravenous immunoglobulin and rituximab. Era before 2005, intensive care unit‐bound status, high Model for End‐Stage Liver Disease score and absence of rituximab prophylaxis were significant risk factors for overall survival and antibody‐mediated rejection (AMR) in the univariate analysis. After adjustment for era effects in the multivariate analysis, only absence of rituximab prophylaxis was a significant risk factor for AMR, and there were no significant risk factors for survival. Rituximab prophylaxis significantly decreased the incidence of AMR, especially hepatic necrosis (p < 0.001). In the rituximab group, other B cell desensitization therapies had no add‐on effects. Multiple or large rituximab doses significantly increased the incidence of infection, and early administration had no advantage. In conclusion, outcomes in adult ABO‐I LDLT have significantly improved in the latest era coincident with the introduction of rituximab.